Comportamiento de componentes agronómicos y de rendimiento bajo dosis creciente de ceniza de madera en Allium cepa L. var. agregatum “cebolla regional” en Zungarococha-Loreto. 2021 - Chavez Magipo, Francisco German (2022)
The experiment "Behavior of agronomic and yield components under increasing dose of wood ash in Allium strain L. var. agregatum "regional onion", in Zungarococha- Loreto. 2021", was held at the facilities of the Workshop of Teaching and Research of Horticultural Plants (TEIPH), of the Faculty of Agronomy-UNAP, located at Km. 4 of the road to Zungarococha, south of the city of Iquitos.The type of research was experimental, explanatory with one independent variable (increasing dose of wood ash) and nine dependent variables (plant height, plant diameter, number of leaves/plant, leaf/plant weight, bulb diameter, total plant weight, number of bulbs/plant, weight of bulbs/plant and weight of bulbs/ha). The objective of the research work was to determine the behavior of the agronomic and yield components under increasing dose of wood ash in Allium strain L. var agregatum "regional onion", in Zungarococha-Loreto. 2021. The experimental design that was used was the Completely Random Block Design, with four treatments and four repetitions. Each experimental unit consisted of 4 rows, 10 plants/row and the sampling unit consisted of four plants/experimental unit. At the end of the experiment we had the following conclusions: Wood ash influences the behavior of agronomic components and crop yield of Allium strain L. var. agregatum "regional onion"; the T4 treatment (3 t of wood ash/ha), presented the best results of the behavior of the agronomic components and crop yield; the T4 Treatment (3 t of wood ash/ha), ranked first in bulb weight yield/ha with 10,200 Kg/ha and in the last place the T1 Treatment (0 t of wood ash), with 4,012.5 Kg/ha; the T4 Treatment (3 t of wood ash/ha), obtained the best economic performance, with a utility of S/.,27,545 .00.